Raging the War Against Inflammation With Natural Products - Attiq, Ali; Jalil, Juriyati; Husain, Khairana; Ahmad, Waqas (Frontiers in Pharmacology, 2018)
Over the last few decade Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are the drugs of choice for treating numerous inflammatory diseases including rheumatoid arthritis. The NSAIDs produces anti-inflammatory activity via inhibiting cyclooxygenase enzyme, responsible for the conversation of arachidonic acid to prostaglandins. Likewise, cyclooxegenase-2 inhibitors (COX-2) selectively inhibit the COX-2 enzyme and produces significantmilar anti-inflammatory, analgesic and anti-pyretic activity without producing COX-1 associated gastrointestinal and renal side effects. Hence during theIn last two decades numerousseveral selective COX-2 inhibitors (COXIBs) have been developed and approved for various inflammatory conditions. However, data from clinical trials have suggested that the prolong use of COX-2 inhibitors are also associated with life threatening cardiovascular side effects including ischemic heart failure and myocardial infection. In these scenario secondary metabolites from natural product offers a great hope for the development of novel anti-inflammatory compounds. Although majority of the natural product based compounds exhibit more selectively towards COX-1. However the data suggest that slight structural modification can be helpful in developing COX-2 selective secondary metabolites with comparative efficacy and limited side effects. Hence thisThis review is an effort to highlight the secondary metabolites from terrestrial and marine source with significant COX-2 and COX-2 mediated PGE2 inhibitory activity,. since it is anticipated thatSince the isolates with ability to inhibit potential to inhibit COX-2 mediated PGE2 production would be useful inare expected to suppressing inflammationthe inflammation and its classical sign and symptoms. Moreover this review has highlighted the potential lead compounds including berberine, kaurenoic acid, α-cyperone, curcumin and zedoarondiol for further development with the help of structure–activity relationship (SAR) studies and their current status.